Transformasi Perilaku Hidup Bersih dan Sehat melalui Kolaborasi Pemberantasan Sarang Nyamuk (PSN) dan Pemeriksaan Kesehatan di Wilayah Endemis - Herlina Yulidia; Alia Andriany; Sintong Halomoan Sianturi; Andrew Ivan Humonobe; Laura Putri Risty Lumban Tobing; Yanti Pesurnay; Hamdiah Ahmar; Rosdiana Naibey; Anjela M.Jitmau; Atira Tilik (Lembaga Pengembangan Kinerja Dosen, 2025)
Malaria remains a major public health challenge, particularly in remote areas. In 2023, 379 cases of malaria were recorded, with the highest number in Maibo Village (111 cases). To address this issue, a Community Service Program (PKM) was conducted, focusing on health checks and malaria screening in Maibo Village as a preventive and promotive effort in controlling the disease. This activity is expected to reduce the burden of malaria in areas with high prevalence rates. This PKM involved three series of activities: Mosquito Nest Eradication (PSN), Malaria Prevention Counseling, and Health Checks. This activity was attended by various parties, including the UNIPA Faculty of Medicine Community Service Committee and Implementers, consisting of the Dean of UNIPA Faculty of Medicine and 15 others, 14 UNIPA Faculty of Medicine Community Service Students Class of 2020, as well as members of the 20/PPA Battalion (Yon Zipur 20/PPA) (24 people), the Aimas Police (9 people), and the Malawili Community Health Center Technical Implementation Unit (UPTD) (5 people). The average age of the respondents who participated in this activity was 35 years, with an age range of 1 to 71 years, and the majority of participants were women (59 people, 39.74%). The examination results showed that 9 people (11.53%) were diagnosed with malaria, while the majority of respondents experienced other complaints, such as skin diseases (23.07%) and muscle pain (15.38%). This indicates an urgent need for integrated health services to address the various complaints that arise in the community. This activity had a positive impact in increasing awareness among the Maibo Village community regarding malaria prevention and the importance of a clean and healthy lifestyle (PHBS). It is recommended that education, regular check-ups, and active community involvement continue to be strengthened.